2020
DOI: 10.1002/mc.23160
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and cancer prevention: Studies with different forms of tocopherols and tocotrienols

Abstract: α‐Tocopherol (α‐T) is the major form of vitamin E (VE) in animals and has the highest activity in carrying out the essential antioxidant functions of VE. Because of the involvement of oxidative stress in carcinogenesis, the cancer prevention activity of α‐T has been studied extensively. Lower VE intake or nutritional status has been shown to be associated with increased cancer risk, and supplementation of α‐T to populations with VE insufficiency has shown beneficial effects in lowering the cancer risk in some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 161 publications
(389 reference statements)
1
78
0
6
Order By: Relevance
“…Some notable examples of variable proteins include the growth hormone 2 (GH2) 29 which shows a large range of expression values and the alpha subunit of the glycoprotein hormones (CGA) which shows the expected higher expression in women than men. In addition, we see that among the most stable metabolites we find gamma (γ)-tocopherol 30 , a form of vitamin E. Evidence of γ-tocopherol effect in preventing endothelial injury, lipid peroxidation, and oxidative stress have been reported 30,31 . Indeed, γ-tocopherol is important in preserving endothelial function by protecting the degradation of tetrahydrobiopterin (BH4), a key cofactor in the synthesis of nitric oxide 32 .…”
Section: Resultsmentioning
confidence: 74%
“…Some notable examples of variable proteins include the growth hormone 2 (GH2) 29 which shows a large range of expression values and the alpha subunit of the glycoprotein hormones (CGA) which shows the expected higher expression in women than men. In addition, we see that among the most stable metabolites we find gamma (γ)-tocopherol 30 , a form of vitamin E. Evidence of γ-tocopherol effect in preventing endothelial injury, lipid peroxidation, and oxidative stress have been reported 30,31 . Indeed, γ-tocopherol is important in preserving endothelial function by protecting the degradation of tetrahydrobiopterin (BH4), a key cofactor in the synthesis of nitric oxide 32 .…”
Section: Resultsmentioning
confidence: 74%
“…Many studies showed a negative association between dietary VE intake or blood levels of VE (mostly a-tocopherol (T)) and cancer risk, suggesting a cancer preventive effect. However, other studies, including some recent largescale intervention studies, did not support the hypothesis that VE is cancer preventive (1,2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In a large chemoprevention trial, the Alpha-Tocopherol, Beta-Carotene Cancer Prevention (ATBC) study, supplementation with VE (given as all rac-a-tocopheryl acetate 50 IU daily) was associated with a 32% decrease in prostate cancer incidence and a 41% decrease in mortality of prostate cancer, when prostate cancer analyzed as a secondary endpoint (11).…”
Section: Introductionmentioning
confidence: 92%
“…Numerous epidemiological studies have investigated the relationship between vitamin E (VE) nutrition and cancer (reviewed in (1)(2)(3)(4)). Many studies showed a negative association between dietary VE intake or blood levels of VE (mostly a-tocopherol (T)) and cancer risk, suggesting a cancer preventive effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These lipophilic compounds are abundant in vegetable oils and nuts and are widely studied as agents with an impact on human health and disease pathogenesis [143][144][145][146][147]. Numerous reviews have covered the topic of vitamin E and cancer [148][149][150][151]. Recently, γ-TmT, a commercially available by-product of vegetable oil refinery containing 57% γ-tocopherol, was linked to induction of the Nrf2 pathway via hypomethylation of the Nfe2l2 promoter in the TRAMP mouse and in TRAMP-C1 cells in vitro.…”
Section: γ Tocopherol-rich Mixture Of Tocopherols (γ-Tmt)mentioning
confidence: 99%